Modified Ultrafiltration and Acute Kidney Injury in Patients Undergoing Open Heart Surgery Using Cardiopulmonary Bypass - Hammad Azam, Ayed Amesh Alshammary, Sajid Farooq, Sahrish Ghaffar, Adeela Shahzadi, Mirza Ahmad Raza Baig, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the incidence of acute kidney injury (AKI) in patients undergoing open heart surgery using cardiopulmonary bypass (CBP) with and without modified ultrafiltration (MUF). Materials and Methods: A total of 150 patients who underwent open heart surgery using CPB in our hospital from Jan-2022 to Dec-2022. In group A patients MUF was performed during the CPB and atleast 1000 ml of volume was removed using MUF. While in group B patients, no filtration was performed during CPB. In ICU all patients were followed till three days after surgery to determine the incidence of AKI. Results: Mean age was 53.4±10.9 years in MUF group versus 55.6±11.8 years in control group, p-value 0.23. Majority, 53 (70.7%) patients were male in MUF and 57 (76%) in control group, p-value 0.55. Mean CPB time was 101.6±45.2 mins in MUF and 96.5±39.1 mins in control group, p-value 0.46. Mean X-clamp time was 47.5±19.3 mins in MUF and 51.4±21.6 mins in control group, p-value 0.43. The incidence of AKI was comparable, with frequency rate of 3 (4.0%) in MUF group versus 1 (1.3%) in control group, p-value 0.31. Conclusion: In present study, the incidence of AKI in MUF and control group was almost similar. So according to the results of present study, the use of MUF has no role in preventing or aggravating AKI in patients undergoing CPB. Keywords: Acute kidney injury, cardiopulmonary bypass, modified ultrafiltration.